2021
DOI: 10.1177/02692163211059342
|View full text |Cite
|
Sign up to set email alerts
|

Paramedics delivering palliative and end-of-life care in community-based settings: A systematic integrative review with thematic synthesis

Abstract: Background: There is a growing demand for community palliative care and home-based deaths worldwide. However, gaps remain in this service provision, particularly after-hours. Paramedicine may help to bridge that gap and avoid unwanted hospital admissions, but a systematic overview of paramedics’ potential role in palliative and end-of-life care is lacking. Aim: To review and synthesise the empirical evidence regarding paramedics delivering palliative and end-of-life care in community-based settings. Design: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 53 publications
1
67
0
1
Order By: Relevance
“…In this, and some previous studies 8,17,19,22,23,32,40 paramedics expressed a need for regular training in end-of-life care. Improving their skills in end-of-life care might reduce feelings of stress.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In this, and some previous studies 8,17,19,22,23,32,40 paramedics expressed a need for regular training in end-of-life care. Improving their skills in end-of-life care might reduce feelings of stress.…”
Section: Discussionmentioning
confidence: 51%
“…Paramedics have an important role in caring for patients in end-of-life care, although this potential task has only recently been recognized and still unfrequently organized. 6,7,9,13,16,17,19,22,23 Previous studies 11,19,23,24,27,32,40 have shown the urgent need for integration of palliative care into the healthcare system, development of palliative care pathways and finally, guidelines for paramedics to treat end-of-life patients. The end-of-life care by paramedics’ needs a shift from a life-saving approach to a relief of suffering 17 and expanding their role from an ambulance transferer to a nurse of end-of-life-patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CP can deliver time-sensitive therapies such as rehydration and nausea control and even lab services [84]. They may provide a bridge to other health professionals, via telehealth or other forms of communication [77,[85][86][87][88][89]. For example, patients under hospice care, for example, may receive pain medication via MIH or CP programs while waiting for the arrival of a hospice nurse.…”
Section: Benefitsmentioning
confidence: 99%